Use of a brief, retrospective Comprehensive Feeding Practices Questionnaire in a bariatric-surgery seeking adult population. (August 2022) - Edwards, Caitlyn G.; Zickgraf, Hana F.; Masterson, Travis D.; Rigby, Andrea
Abstract: Parental feeding practices in childhood have been shown to contribute to childhood eating habits, behaviors, and weight status. Less understood is the longitudinal impact of parental feeding practices on these variables in adulthood. Therefore, the aim of the present work was to validate a modified, brief, Comprehensive Feeding Practices Questionnaire (CFPQ) reformatted to account for retrospective recollections of parental feeding practices experienced in childhood among a sample of adults with obesity. Adults (n = 719, mean age = 44.3 years, mean BMI = 47.1 kg/m 2 ) completed a modified, brief, retrospective CFPQ containing seven pre-defined subscales of the original CFPQ. Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) procedures were used to evaluate survey factor structure and associations with gender, BMI, and self-reported race. An EFA derived six-factor model demonstrated better model fit and reliability than the originally proposed seven-factor model. Gender and self-reported race were not correlated with subscales of the brief, retrospective, CFPQ, while BMI was positively correlated with the Food as Reward subscale. This six-factor, brief, retrospective, CFPQ can be used to provide insight into the potential origins of individual eating behaviors, and warrants use in future work attempting to clarify the relationships between parental feeding practices and eating behaviors in adulthood. Highlights: Parental feeding practices contribute to childhood eating habits and behaviors. Recollections of parental feeding practices may inform eating behavior in adulthood. A brief, retrospective CFPQ can be used to assess recollections of parental feeding practices.